PENGARUH PEMBERIAN REWARD SIMON STIKER EMOTIKON DALAM PENINGKATAN KEDISIPLINAN ANAK USIA 4-5 TAHUN (Sindoro: Cendikia Pendidikan, 2025)
This research highlights the importance of applying reward methods, especially the use of Emoticon Stickers (SIMON), in improving the discipline of children aged 4-5 years. The focus of this study is to see the effect of rewarding SIMON (Emoticon Stickers) in increasing the discipline of children aged 4-5 years. The method used is a quantitative method with a pretest-posttest control group design. The observation sheet used has been validated by experts in the field of early childhood psychology on the discipline of children aged 4-5 years. The validation method through expert judgment is used to determine the achievement indicators in the discipline assessment. The effectiveness of SIMON media was measured through the comparison of the total scores of the pretest and posttest. Sampling using simple random sampling technique involved 25 children. Data were collected through observation, and analyzed using the Wilcoxon test. The results showed a significant effect on children's discipline after giving rewards. This is evidenced by the sig value of 0.0001 which is less than the predetermined significance level value of 0.05. The effect of giving SIMON (Emoticon Sticker) rewards is effective in improving children's discipline. This is indicated by the posttest value which is higher than the pretest value. With these results, it can be concluded that giving SIMON (Emoticon Stickers) rewards can have a positive and significant effect so that it becomes an initial impetus for children to learn discipline. Penelitian ini menyoroti pentingnya penerapan metode reward, khususnya penggunaan Stiker Emotikon (SIMON), dalam meningkatkan kedisiplinan anak usia 4-5 tahun. Fokus pada penelitian ini adalah  untuk melihat adanya pengaruh dari pemberian reward SIMON (Stiker Emotikon) dalam peningkatan kedisiplinan anak usia 4-5 tahun. Metode yang digunakan adalah metode kuantitatif dengan desain penelitian pretest-posttest control group design. Lembar observasi yang digunakan telah divalidasi oleh ahli dalam bidang psikologi anak usia dini terhadap kedisiplinan anak usia 4-5 tahun. Metode validasi melalui expert judgement digunakan untuk menetapkan indikator capaian dalam penilaian kedisiplinan. Keefektifan media SIMON diukur melalui perbandingan nilai total pretest dan posttest. Pengambilan sampel menggunakan teknik simple random sampling melibatkan 25 anak. Data dikumpulkan melalui observasi, dan dianalisis menggunakan uji wilcoxon. Hasil penelitian menunjukkan adanya pengaruh yang signifikan pada kedisiplinan anak setelah pemberian reward. Hal ini dibuktikan dengan nilai sig sebesar 0,0001 yang kurang dari nilai tingkat signifikansi yang telah ditetapkan yaitu 0,05. Pengaruh pemberian reward SIMON (Stiker Emotikon) efektif dalam meningkatkan kedisiplinan anak. Hal ini ditandai dengan nilai posttest yang lebih tinggi dibandingkan nilai pretest. Dengan hasil tersebut didapatkan kesimpulan bahwa pemberian reward  SIMON (Stiker Emotikon) dapat memberikan pengaruh yang posotif dan signifikan sehingga menjadi pendorong awal bagi anak untuk belajar disiplin.